Mobilizing Territory: Socioterritorial Movements in Comparative Perspective - Halvorsen, Sam; Mancano Fernandes, Bernardo [UNESP]; Valeria Torres, Fernanda (Routledge Journals, Taylor & Francis Ltd, 2019)
Why does territory matter to social movements and what does it allow them to achieve? Despite the ever-apparent centrality of territory-the appropriation and control of space through forms of power-to social movements worldwide (e.g., protest camps, land occupations, indigenous activism, squatting, neighborhood organizing), there has been a surprising lack of attention to this question by Anglophone geographers. This article develops Brazilian geographer Fernandes's notion of socioterritorial movements as an analytical category for social movements that have as their central objective the appropriation of space in pursuit of their political project. It does so by contrasting the concept of socioterritorial movement to those of social movement and sociospatial movement and proposing four axes of analysis for socioterritorial movements. First, territory is mobilized as the central strategy for realizing a movement's aims. Second, territory informs the identity of socioterritorial movements, generating new political subjectivities. Third, territory is a site of political socialization that produces new encounters and values. Fourth, through processes of territorialization, deterritorialization, and reterritorialization, socioterritorial movements create new institutions. These axes are further elaborated through the comparative analysis of two case studies: the Movimento dos Trabalhadores Rurais Sem Terra, a large peasant movement in Brazil, and the Tupac Amaru Neighborhood Organization, an urban social movement from northwest Argentina. Comparison is deployed as an expansive mode of analysis to open up the concept of socioterritorial movement and indicate potential lines of enquiry for further study.
Keywords: Argentina; MST; social movements; socioterritorial movements; territory